Antioxidant properties of mashua (Tropaeolum tuberosum) phenolic extracts against oxidative damage using biological in vitro assays - Chirinos R. (2008)
We thank Dr. Carlos Arbizu, International Potato Center (Lima, Peru) for providing the mashua genotypes and Alexandrine During and Yves-Jacques Schneider for their suggestions in the discussion of this paper. This research was supported by the CUI project of the Belgian Coopération Universitaire au Développement (CUD, Belgium) and by the Consejo Nacional de Ciencia y Tecnología (CONCYTEC, Peru).